Kepala Madrasah sebagai Supervisor Akademik untuk Meningkatkan Kinerja Guru MTs N Donomulyo Kulonprogo - Latief, Jamroh; Masruroh, Nur Afifah (Prodi Manajemen Pendidikan Islam FITK UIN Sunan Kalijaga Yogyakarta, 2016)
This research explores the role of Madrasa’s headmaster as an academic supervisor to improve teacher’s performance in State Islamic Junior High School (MTs) of Donomulyo, Kulon progo, Yogyakarta. This is a qualitative research using non participatory observation method, interview and documentations as its data collection.  The result shows that: (1).  MTs Donomulyo employs assistance as the academic supervision concept, (2). the academic supervision programs applied to improve teachers performances are training and development for individual teachers or in group, (3). Madrasa’s headmaster’s role in the improvement of teachers’ performances involves guiding them in the form of giving motivation, encouragement, as well as giving examples. Beside that, he is also sometimes suggest for a solution, help, building commitment and training.